A taxonomic revision of the genus Antiphiona (Inuleae, Asteraceae), including a report of the first collection of the genus for South Africa - Koekemoer, Marinda (Phytotaxa, 2018)
A new distribution record for Antiphiona pinnatisecta is reported for South Africa for the first time. A key to the species as well as descriptions in English and updated specimen and distribution records are provided. Micrographs of the important characters and images of the new distribution locality are included.